1985
DOI: 10.1007/bf00044767
|View full text |Cite
|
Sign up to set email alerts
|

The significance of waterfowl grazing in the primary vegetation succession on embanked sandflats

Abstract: In the annual stage of a primary plant succession on desalinating sandflats of the Lauwerszeepolder, N Netherlands, grazing by waterfowl is a dominant factor, as is illustrated by exclosures. It is concluded from population dynamical data, that both the removal of biomass and the predation of seeds sustain the annual species and retard succession towards the next stage of a perennial grassland by several years. Yearly mowing in September slightly enhances succession by selectively affecting the dominant annual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…86,No. 4 velopment (Joenje 1985, Rowcliffe et al 1998. The present study suggests that these effects are no longer visible over longer time scales.…”
Section: Goose and Hare Herbivorymentioning
confidence: 50%
“…86,No. 4 velopment (Joenje 1985, Rowcliffe et al 1998. The present study suggests that these effects are no longer visible over longer time scales.…”
Section: Goose and Hare Herbivorymentioning
confidence: 50%
“…This has been shown for a variety of ecosystems, e.g. salt-marshes grazed by waterfowl (Joenje 1985; our 1992) and cattle (Bakker 1985(Bakker , 1989Andresen et al 1990), dune grasslands grazed by rabbits (Watt 1957;Zeevalking & Fresco 1977), coastal tundras grazed by lemmings (Batzli et al 1980), and savannas grazed and browsed by large herbivores (see McNaughton & Georgiadis 1986;Prins 1989;Prins & Van der Jeugd 1993). As soon as the density of herbivores becomes reduced by some external factor, below the level of the carrying capacity, the rate of vegetation succession increases.…”
Section: Biogenic Causes Of Vegetation Successionmentioning
confidence: 64%
“…The salinity of the 0-5 cm soil layer is relatively high in the Festuca-Limonium community ( Table 1). The very open canopy in the heavily grazed area in the Festuca-Limonium and in the Artemisia maritima community might enhance evapotranspiration and hence cause the salinity of the topsoil to be higher (Joenje 1985). Moreover, the uppermost cm in grazed sites reached a higher salinity in grazed than in abandoned sites in the study area (Bakker, Dijkstra & Russchen 1985).…”
Section: Discussionmentioning
confidence: 94%
“…Although lower salt-marsh species generally spread higher up on the salt marsh in our study area, both the annual and perennial species were not found every year, but showed an irregular pattern of occurrence (Bakker 1989). Their occurrence in grazed salt marshes (Christiansen 1937;Schmeisky 1977;Hansen 1982) and desalinating embanked flats (Westhoff & Sykora 1979;Joenje 1985) as compared to exclosures, is a general phenomenon. Unfortunately, no literature on the comparison of grazing and mowing of salt marshes is available.…”
Section: Discussionmentioning
confidence: 99%